Competitive Improvement Strategies of The Coconut Oil Industry at PT XYZ - Aulia Ramadhan, Muhammad; Heryawan Asnawi, Yudha; Jahroh, Siti (Journal Research of Social Science, Economics, and Management, 2024)
This study aims to develop strategies for enhancing competitiveness in the coconut oil industry amidst intense competition. It analyzes the internal and external conditions of PT XYZ, focusing on optimizing strengths and opportunities while leveraging an Initial Public Offering (IPO) strategy. The study examines the internal and external conditions of PT XYZ to develop strategies for improving competitiveness. Utilizing qualitative methods, the research employs analytical tools such as the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, SWOT analysis, and the Quantitative Strategic Planning Matrix (QSPM). The sample consists of 15 respondents, including 11 internal and 4 external participants. Results show that the company’s internal conditions, with 5 strengths and 4 weaknesses, yield an IFE score of 3.03. In contrast, the external conditions, featuring 5 opportunities and 4 threats, result in an EFE score of 2.92. This analysis places PT XYZ in Quadrant IV of the IE matrix, indicating a "grow and build" strategy, as both scores exceed the average benchmark of 2.50. These findings highlight significant potential for continuous improvement in strategy and operations. The next step involves formulating alternative strategies through the SWOT method, generating eight options based on the analysis. Ultimately, the QSPM identifies three primary strategies with the highest total scores: increasing production capacity to enhance revenue and market share, developing innovative products and services, and implementing business processes adhering to Good Agricultural Practice (GAP) standards. This study provides actionable insights for PT XYZ to bolster its competitiveness in the coconut oil industry.